Elaboració i desenvolupament d'un llibre multimèdia sobre programació matemàtica - Begoña Font Belaire (Servei de Formació Permanent i Innovació Educativa, Universitat de València, 2008)
The edition of handbooks adapted to the self-learning paradigm and using the advantages of the information and communication  technologies (ICT) is basic in the educational innovation processes' success that the Spanish university is involved. This article describes the characteristics that a good electronic book should have. It proposes a methodology for the development of electronic books, shows that this method can be successfully implemented, and presents an example of that: the e-book titled Programación matemática para la economía y la empresa.